Sifat Dan Morfologi Wood Plastic Composite Berbasis Pelepah Sawit Dan Polyethylene Dengan Kompatibilizer Maleic Anhydride Dan Inisiator Dicumyl Peroxide - Afrilla, Nurul; HS, Irdoni.; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The availability of wood in Indonesia is increasingly limited due to forest degradation and increased demand for wood. One of the efforts to reduce the use of wood directly is to develop the manufacture of Wood Plastic Composite (WPC). WPC consists of matrix, filler, and additives such as compatibilizer and initiator which is useful to increase the value of the mechanical properties and physical properties of the WPC. This study aims to determine the effect of maleic anhydride (MAH) compatibilizer with Dicumyl peroxide (DCP) initiator on the properties and morphology of WPC produced, and determine the effect of palm frond (SPS) / HDPE powder ratios on the properties and morphology of WPC. SPS composition is 80mesh and polyethylene is 50:50, 60:40, 70:30 with 3%, 4%, 5% MAH additive mixture, 1% DCP and 2% paraffin. The palm fronds were prepared using oxalic acid at 120ºC with 15 minutes soaking. The process of mixing filler, matrix, and additives using Labo Plastomill internal mixer at 150ºC and 80 rpm rotor speed. Composites produced were tested including physical properties, mechanical properties and morphological tests. The results showed that the mixing ratio of SPS / HDPE and the addition of compatibilizer affected the value of physical properties and mechanical properties of the WPC. The best WPC material was obtained in the mixing ratio of SPS/PE (50/50) with the addition of 5% MAH with 26.631 MPa tensile strength, 2106.4 MPa MOE, 51.23 MPa flexural strength, 1.16 gr / cm3 density, 0.92% water absorption, and 0.17% absorption thickness.Keywords: maleic anhydride, palm frond, polyethylene, wood plastic composite